Strategi Pendampingan Peserta Didik Berkebutuhan Khusus Dalam Pengembangan Sosial Emosional Berbasis Montessori - Ane, Syirilia Regina; Monica Novita Sari; Yuliana Tuto Soromaking; Gregorius Ari Nugrahanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the need to understand Montessori-based mentoring strategies in supporting the social-emotional development of students with special needs. This article aims to examine the mentoring of students with special needs in social-emotional development based on Montessori. This study uses a qualitative descriptive approach and was conducted at a Montessori elementary school in Yogyakarta from February to May 2025. Research data were collected through participatory observation, in-depth interviews, and documentation. The subjects of this study were teachers and lower and upper grade students at a Montessori elementary school in Yogyakarta. The objects of this study were Montessori mentoring and the social-emotional development of students with special needs. Data validity was checked using triangulation. Data were analyzed using Miles & Huberman's qualitative analysis, which involves data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the social-emotional support strategies implemented are based on combining the principles of PDBK management with the Montessori Learning Pyramid structure. The application of the Montessori method has proven effective in developing the social-emotional skills of PDBK.